Localized lepromatous leprosy - Khalid M. Alwunais (Wolters Kluwer Medknow Publications, 2015)
Lepromatous leprosy is usually generalized at diagnosis and may consist of erythematous macules, papules and nodules containing abundant Mycobacterium leprae and affecting wide spread areas of the skin. Localized skin involvement by lepromatous leprosy is rare. In this report a 37 year old Filipino man presented with erythematous lesions localized on the right elbow and left knee for 9 months associated with diminished sensation. Clinically the patient presented with localized lesions mimicking tuberculoid leprosy, although a biopsy from the lesion revealed lepromatous type leprosy. A skin biopsy showed numerous acid fast bacilli and fat laden macrophages with a paucity of lymphocytes, Slit skin smear examination for M. leprae from the lesion revealed a Bacteriological Index (BI) of 6+ which is compatible with lepromatous leprosy.